Self-assembling nanoprobes that display two-dimensional fluorescent signals for identification of surfactants and bacteria. Issue 7 (3rd January 2019) - Long, Shuangshuang; Qiao, Qinglong; Deng, Fei; Miao, Lu; Yoon, Juyoung; Xu, Zhaochao
Abstract : The imidazolium-pyrene self-assembling nanoprobes can rapidly discriminate four types of surfactants. Abstract : The imidazolium-pyrene self-assembling nanoprobes can rapidly discriminate four types of surfactants. The surfactants disassembled the probes to turn on significant fluorescence and transform between a pyrene monomer and an excimer, generating a two-dimensional analysis map. The probes were further used to identify different bacterial species.